Коммуникативные аспекты католических богослужений на русском языке - Wideł-Ignaszczak, Małgorzata (Studia Rossica Posnaniensia, 2019)
The paper is concerned with the aspects of communication during the acts of worship by Russian Catholics. The liturgy and rites are performed in contemporary Russian language. The material was excerpted from the Catechism of the Catholic Church. The paper provides a description of the liturgical model of interpersonal communication during services and the linguistic indicators of its components. The units were grouped according to the criterion of participation in the communication situation involving the sender, the receiver and the communication channel, i.e. liturgy.